Draft genome of an iconic Red Sea reef fish, the blacktail butterflyfish (Chaetodon austriacus): Current status and its characteristics - Di Battista, Joseph; Wang, X.; Saenz-Agudelo, P.; Piatek, M.; Aranda, M.; Berumen, M. (Wiley-Blackwell, 2018)
Butterflyfish are among the most iconic of the coral reef fishes and represent a model system to study general questions of biogeography, evolution and population genetics. We assembled and annotated the genome sequence of the blacktail butterflyfish (Chaetodon austriacus), an Arabian region endemic species that is reliant on coral reefs for food and shelter. Using available bony fish (superclass Osteichthyes) genomes as a reference, a total of 28 926 high-quality protein-coding genes were predicted from 13 967 assembled scaffolds. The quality and completeness of the draft genome of C. austriacus suggest that it has the potential to serve as a resource for studies on the co-evolution of reef fish adaptations to the unique Red Sea environment, as well as a comparison of gene sequences between closely related congeneric species of butterflyfish distributed more broadly across the tropical Indo-Pacific.